Analisis Pengembangan Metode Pembelajaran Kosakata Bahasa Arab untuk Meningkatkan Kemampuan Dakwah dan Komunikasi di Kalangan Mahasiswa - Gymnastiar, Abdullah Aly; Burhanuddin, Burhanuddin (Indonesian Journal Publisher, 2024)
In the context of higher education institutions, Arabic language learning often faces significant challenges in meeting the needs of students who will later be involved in da'wah and communication activities. One of the main obstacles is the criteria for being considered less capable. This research aims to provide an in-depth understanding of the problems and potential solutions in learning Arabic vocabulary among students who focus on da'wah and communication. In this research, the research method chosen is the library method. This means that the research is focused on reviewing and analyzing literature that is relevant to the research topic, namely the development of Arabic language learning methods. Through this method, researchers can explore various literary sources such as books, articles, journals and theses related to teaching Arabic language knowledge. This research shows that the integration of Arabic language learning methods, such as Tarjamah Grammar, Direct, Reading, Audiolingual, and Eclectic approaches, is expected to improve students' Arabic language skills.